Hotelling Models with Price-Sensitive Demand and Asymmetric Transport Costs: An Application to Public Transport Scheduling - Adriaan Hendrik van der Weijde; Erik T. Verhoef; Vincent A. C. van den Berg (Tinbergen Institute, 2012)
We formulate a horizontal differentiation model with price-sensitive demand and asymmetric transport costs, in the context of transport scheduling. Two competitors choose fares and departure times in a fixed time interval. Consumers are distributed uniformly along the interval; their location indicates their desired departure time. In a standard Hotelling model, locations are chosen before prices. In our context, the opposite order is also conceivable, but we show that it does not result in a Nash equilibrium; the same is true for a game in both variables are chosen simultaneously. We also discuss Stackelberg game structures and second-best regulation. We conclude that the addition of price-sensitive demand results in equilibria in the traditional Hotelling model with price setting; there, services are scheduled closer together than optimal. We also show that it is possible to include asymmetric schedule delay functions. Our results show that departure times can be strategic instruments. Optimal regulatory strategies depend on the value of schedule delay, and on whether the regulator can commit.
urn:NBN:nl:ui:31-1871/39443
Keywords: L11; L51; L91; R40; 330; horizontal differentiation; scheduling; transport; Scheduling-Verfahren; Preisdifferenzierung; Transportkosten; Duopol; Hotelling-Modell; Theorie